Biological and molecular characterization of a sheep pathogen isolate of Mannheimia haemolytica and leukotoxin production kinetics - Dounia Bkiri; Noha Semmate; Zineb Boumart; Najete Safini; Fatima Zohra Fakri; Zahra Bamouh; Khalid Omari Tadlaoui; Siham Fellahi; Noursaid Tligui; Ouafaa Fassi Fihri; Mehdi El Harrak (Veterinary World, 2021)
Background and Aim: Mannheimia haemolytica (Mha) is a common agent of pneumonia in ruminants globally, causing economic losses by morbidity, mortality, and treatment costs. Infection by Mha is often associated with or promoted by respiratory viral pathogens and environmental conditions. Infections due to Mha have rarely been described in small ruminants. This study reports the biological and molecular characteristics of a new Moroccan Mha isolate from small ruminants presenting typical respiratory symptoms. We also studied the cultural parameters, growth kinetics, and Lkt excretion of the isolate and its pathogenicity on laboratory animals and small ruminants.